Aníbal Pinto, Schumpeter e Friedman em um coquetel: Uma proposta de sistema de capacitaç\~ao e financiamento do aumento da produtividade das MPEs com pagamento quando e se o negócio prospera - Mauro Oddo Nogueira; Paulo A. Meyer M. Nascimento; Luiz A. Esteves; Giovanni Silva Beviláqua; Fabiano Mezadre Pompermayer (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
We propose an integrated public-private system designed to improve the pre-finance capabilities of micro and small enterprises (MSE), thereafter assisting them with finance to foster their innovation and/or expansion plans. The idea is to regulate a market standing on income-contingent financing, an important social innovation that has transformed student financing in Australia and England and has been increasingly discussed in the literature on public financing as an improvement over previous mechanisms for funding investment in several other areas besides education. Income-contingent financing implies that the side providing the funds receives back a proportion of the future income, revenue, or profits of the person or firm being funded, as repayment of a loan or as remuneration for an investment made. Given that the proposal presented in this paper focuses on firms, we will refer to the mechanism as revenue-contingent financing. To make such an arrangement viable in Brazil, a new tax is needed. The new tax is the way to involve the federal revenue system in the repayment collection, thus taking advantage of the economies of scale and scope involved in the State's power to tax in order to remove failures in the capital market. The removal of such market failures leads to social benefits greater than the private benefits eventually earned, justifying the introduction of a new tax to collect revenue-contingent repayments. The proposed arrangement reduces the risks of non-repayment, increasing the guarantees for those who provide finance. As repayments occur only if and when the firm's revenue is greater than a predetermined level, revenue-contingency also insures firms against negative shocks. In our proposed system, eligibility for financing is linked to a previous managerial training, at the end of which entrepreneurs shall submit a business plan, and this must be certified by an independent agency outside the institution where the managerial training took place. The certified business plan then works as a kind of "recommendation letter" to be taken to accredited financial institutions for the granting of either debt or equity revenue-contingent instruments. To some extent, this proposal combines three strands of economic thought that are quite distinct from each other: structuralism, the Schumpeterian approach, and liberalism. It relies, in particular, on elements risen by Aníbal Pinto, Joseph Schumpeter and Milton Friedman - that is the reason why these three thinkers are mentioned in the title of this paper.
Keywords: G28; H25; L26; 330; micro and small businesses; entrepreneurship; financing; credit instruments; public policy; contingent income loan; income share agreements